PENGARUH OWNERSHIP STRUCTURE, DAN BOARD GOVERNANCE TERHADAP DIVIDEND YIELD (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Advento Johanes Pangomo; Irene Rini Demi Pengestuti Pangestuti (JURNAL STUDI MANAJEMEN ORGANISASI, 2018)
This research aims to examine the effect of corporate governance on dividend yield. The ownership structure is devided to instituitional ownership, ownership concentration, managerial ownership  and board governance is divided to board size, board independence, intensity as independence variables, while dividend yield as dependent variable. Fim age, firm size, debt, and return on equity are also added as control variable. This reseach used secondary data with population consists of 144 manufacturing companies listed in Indonesia Stock Exchange in the period of 2012-2016. The purposive sampling method used was used in selecting the research sample and 28 manufacturing companies that consistently distributed dividends during the research period. Multiple regression technique are chosen for this research statistic analysis. The result of this research shows that institutional ownerhip, and intensity has a positive significant effect on the dividend yield, but board independence has a negative significant effect on the dividend yield. Meanwhile, ownership concentration, managerial ownership, and board size have no significant effect on the dividend yield.